Second-generation cryoballoon-based pulmonary vein isolation: Lessons from a five-year follow-up. (1st August 2020) - Heeger, Christian-Hendrik; Subin, Behnam; Wissner, Erik; Fink, Thomas; Mathew, Shibu; Maurer, Tilman; Lemes, Christine; Rillig, Andreas; Wohlmuth, Peter; Reissmann, Bruno; Tilz, Roland Richard; Ouyang, Feifan; et al.
Abstract: Background: Pulmonary vein isolation (PVI) using the second-generation cryoballoon (CB2) for atrial fibrillation (AF) treatment has demonstrated encouraging procedural success rates and mid-term results. However, long-term follow-up data on outcome is sparse. The current study is reporting on five-year clinical outcomes following CB2-based PVI in patients with paroxysmal AF (PAF) and persistent AF (PersAF). Methods: A total of 139 patients underwent index CB2-based PVI patients (PAF: n = 105, 76% and PersAF: n = 34, 34%) in two electrophysiology centers. Freeze-cycle duration was 240 s. After successful PVI a bonus freeze-cycle of the same duration was applied in the first 71 patients while the bonus-freeze was omitted in 68 following patients. Three patients (2.2%) were lost to follow-up. Results: After a median follow-up duration of 60 months (interquartile range: 46, 72 months) 74/136 (54.4%) patients remained in stable sinus rhythm (PAF: 62/104, 59.6%; PersAF: 15/32, 46.9%). Significant differences were observed concerning 5-year clinical outcome between PAF and PersAF patients (p = 0.0315). After a mean of 1.32 ± 0.6 procedures (2nd and 3rd procedure by radiofrequency ablation) and a median follow-up duration of 60 (37, 68) months 90/136 (66.2%) patients remained in stable sinus rhythm (PAF: 72/104 (69.2%), PersAF: 21/32 (65.6%), p = 0.0276). For the comparison of bonus-freeze vs no-bonus-freeze protocols no differences were observed (53.5% vs 57.4%, p = 0.650). Conclusions: The five-year single-procedure success rate for CB2-based PVI was 54.4% and increased to 66.2% following repeat RF-based procedures. No differences were detected comparing bonus-freeze and no-bonus-freeze protocols. Highlights: Five-year clinical outcome following CB2 PVI was 54.4% (PAF: 59.6%; PersAF: 46.9%). Significant differences were found for 5-year outcome between PAF and PersAF (p = 0.0315). Multiple procedure outcome was 66.2% (PAF: 69.2%, PersAF: 65.6%), p = 0.0276. Bonus-freeze vs no-bonus-freeze comparisons found no differences (p = 0.650).